Globalization of highly indebted countries: some issues - Majumdar, Bhaskar (1998)
The countries in the Third World, particularly the Highly Indebted Countries (HICs), at the turn of the twentieth century, are believed to have no options but to remain integrated in the International Economic Order (IEO) shaped by the Developed Market Economics (DMEs) under the leadership of the United States. This IEO which was shaped during post-Second World War period got consolidated following the disintegtration of the USSR and the fall of the Berlin Wall in 1989. The paper is an attempt to identify the economic structural dimensions of these HICs that cause their subjugation in this IEO. This paper aims to explore the possibilities of these HICs to develop the power that enables each country and the group as a whole to assert itself in the IEO. The focus is primarily on development of national power through setting and executing project determined by the nation-specific socio-economic priorities for each of these HICs if they cannot form a group or bloc to delink themselves from the given IEO. - Reproduced
Keywords: Globalization